2014
DOI: 10.2994/sajh-d-14-00032.1
|View full text |Cite
|
Sign up to set email alerts
|

Big, Bad, and Beautiful: Phylogenetic Relationships of the Horned Frogs (Anura: Ceratophryidae)

Abstract: The horned frog family, Ceratophryidae, currently comprises three genera and 12 extant species, distributed from the Caribbean lowlands to the Pampean grasslands. Horned frogs are fossorial species that are remarkable in terms of their adult and larval morphology, karyotype, behavior, and other aspects of their biology. In this paper we present a molecular phylogenetic analysis with the goals of: (1) exploring the relationships among the species of Ceratophryidae; (2) studying the evolution of polyploidy; (3) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 147 publications
(233 reference statements)
2
49
0
1
Order By: Relevance
“…Although the L. laevis genome still awaits sequencing, genome-independent proteomic strategies have recently been shown to be feasible for non-model species (Wuhr et al, 2014). Since L. laevis is a diploid organism (Faivovich et al, 2014), sequencing and assembly of its genomic sequence should be less cumbersome than for the pseudotetraploid X. laevis . Moreover, a draft transcriptome assembly from embryonic organs contains greater than 26,000 predicted L. laevis proteins [including over 10,000 full-length ORFs with significant similarity to human proteins (BLAST e value of less than 10 −5; N.M.A., N.N.-Y.-unpublished data)]; thus, what we learn in this large-egged cannibalistic frog has great potential to provide insight into bio-medically relevant biology.…”
Section: Discussionmentioning
confidence: 99%
“…Although the L. laevis genome still awaits sequencing, genome-independent proteomic strategies have recently been shown to be feasible for non-model species (Wuhr et al, 2014). Since L. laevis is a diploid organism (Faivovich et al, 2014), sequencing and assembly of its genomic sequence should be less cumbersome than for the pseudotetraploid X. laevis . Moreover, a draft transcriptome assembly from embryonic organs contains greater than 26,000 predicted L. laevis proteins [including over 10,000 full-length ORFs with significant similarity to human proteins (BLAST e value of less than 10 −5; N.M.A., N.N.-Y.-unpublished data)]; thus, what we learn in this large-egged cannibalistic frog has great potential to provide insight into bio-medically relevant biology.…”
Section: Discussionmentioning
confidence: 99%
“…In Ceratophrys , values range from 20–24 days in wild C. cranwelli to 25–32 days in C. stolzmanni (Fabrezi et al, ; Ortiz, Almeida‐Reinoso, & Coloma, ) and 70 days in C. aurita (Miranda‐Ribeiro, ); in C. ornata , periods from 20 to 32–36 days have been reported (Honegger, Schneider, & Zimmermann, ; Natale et al, ). Faivovich et al () suggested that ceratophryids diversified early in semiarid environments, and three independent transformations resulted in C. aurita , C. ornata , and C. cornuta , which occupy tropical or temperate humid areas. In this context, it seems possible that ancestral short larval periods may have lengthened along with habitat diversification.…”
Section: Discussionmentioning
confidence: 99%
“…Last, the relationship between ploidy levels and developmental rates should be explored in Ceratophryidae, which is unusual in including multiple polyploid species (Faivovich et al, ). Polyploidy is an important evolutionary phenomenon that causes the whole‐genome multiplication and a consequent genomic redundancy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Burrowing may be the single most common adaptation for avoiding desiccation among anurans from deserts, savannas, and other dry environments (Main et al 1959, Wells 2007. Additionally, ceratophryids develop a cocoon of dead skin to reduce water loss during aestivation (Faivovich et al 2014). This cocoon has been considered a specialization associated with semiarid environments (McClanahan et al 1976).…”
Section: Prey Category F (%) N (%) V (%) Imentioning
confidence: 99%